Bovarism as solitude. Hanne Ørstavik’s Love as a novel about the Norwegian Madame Bovary of the 1990’s - Maria Sibińska (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
This article starts out with a brief survey of literary history, showing the introduction of Bovarism in 19th century Norwegian literary circles. Using Amalie Skram’s novel Constance Ring as an example, the author of the article argues that the first phase of Bovarism in Norway appears as a voice in the feminist debate from that period. However, the major emphasis of the article is a reading of Hanne Ørstavik’s Love, one of the most important Norwegian novels of the 1990’s, whose protagonist is frequently characterized by Scandinavian literary scholars as a modern Madame Bovary. The article describes the Bovary-like qualities of the protagonist, while emphasizing her self-centeredness and her narcissism, which result in her loneliness.